Strength properties of single dowel joint using kelempayan wood and oil palm trunk / Mohd Fazli Abu Hassan, Ahmad Fauzi Awang @ Othman and Asnawi Serailla - Abu Hassan, Mohd Fazli; Awang @Othman, Ahmad Fauzi; Serailla, Asnawi (2015)
T-shape joints are widely used in furniture part installation, commonly applied in chair or desk for its rail and stretcher. Recently, detailing or dimension of joints was based on trial-and-error methods and was largely a matter of traditional. The strength structural of furniture depends on how strong that joint can hold the load for some period of time. It is necessary to identify the potential of joints with a specified strength to enhance the weakest joint system. This study was undertaken accordingly to obtain the strength of single dowel pin joint with different diameter sizes and length of straight dowels (6mm x 35mm, 8mm x 40mm, 10mm x40mm) and Poly Vinyl Acetate (PVAc) as glue. The dowel pin joint will be tested on two different wood; kelempayan wood and oil palm trunk (OPT). This is to determine either the three sizes of dowel have significant effect on the two types of wood. If these sizes are significant, it will save the furniture production in terms of its cost. The testing result was analyzed using SPSS. The result analyzed using ANOVA through Least Significant Differential (LSD) with confident level 95%. The data shows for both species have significant value for three testing. It was determined when P-value is < 0.05. According to ANOVA, OPT recorded their P-value are P=0.025 for Maximum Load, P=0.030 for Tensile at Break and P=0.000 for Load at Break. For Kelempayan wood, it P-value are P=0.036 for Maximum Load, P=0.011 for Tensile at Break and P=0.000 for load at Break. Based on this result, all dowel sizes have a significant strength for all testing. The gradual increasing of dowel size will affect the joint strength by big contact between two adherents.